The Effects of language learning strategy training on the speaking and listening skills of an adult EFL learner a case study - Malazo, Czarinah; Jogno, Diane Erica C.; Llenado, Patricia Camille S. (College of Arts and Letters, University of the Philippines Diliman, 2012)
In this age of the Internet and high-end electronic gadgets, there is a need to reexamine the roles of both the English as a Foreign Language (EFL) learner and the teacher. Efforts should be made by practitioners to help promote autonomy in EFL learning. One way to achieve this is through language learning strategy (LLS) training. An experimental case study was conducted to identify the effects of strategy training on an EFL learner's listening and speaking skills and affect. Rebecca Oxford's Strategy Inventory for Language Learning was used in identifying the LLS of the learner. Results showed that the most frequent used strategies were compensation strategies, metacognitive strategies, and cognitive strategies. The least used strategies were affective strategies, social strategies, and memory strategies. The learner's listening and speaking skills on the initial and final parts of the training were described, analyzed, and compared using the rubrics based on the American Council for the Teaching of Foreign Languages (ACTFL) Proficiency Guidelines. Based on the rubrics, the level of the learner's listening and speaking skills prior to the strategy training was Novice Mid. After the training, the learner exhibited performance which was pertinent to Novice High. Diary entries written by the learner on the final parts reflected feelings of satisfaction and pleasantness. A significant contribution this study made was that it examined the effects of strategy training on the listening and speaking skill and on the affect of a novice EFL learner in an online leaning environment. It gave a fresh perspective on language learning strategy research. Future researchers can undertake a similar research by having a bigger sample size. Standardized assessments such as the ACTFL Oral Proficiency Interview or other language tests can be used in assessing the listening and speaking skills of the learner.